2021
DOI: 10.1016/j.redox.2021.101966
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle-specific Keap1 disruption modulates fatty acid utilization and enhances exercise capacity in female mice

Abstract: Skeletal muscle health is important for the prevention of various age-related diseases. The loss of skeletal muscle mass, which is known as sarcopenia, underlies physical disability, poor quality of life and chronic diseases in elderly people. The transcription factor NRF2 plays important roles in the regulation of the cellular defense against oxidative stress, as well as the metabolism and mitochondrial activity. To determine the contribution of skeletal muscle NRF2 to exercise capacity, we conducted skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…Similarly, one of the NRF2-inducing phytochemicals, curcumin, improves exercise performance in mice with heart failure [ 166 ]. Moreover, genetic activation of NRF2 in skeletal muscles increases the slow oxidative muscle fiber type and improves exercise endurance capacity in female mice [ 167 ].…”
Section: Tissue Aging and The Keap1-nrf2 Systemmentioning
confidence: 99%
“…Similarly, one of the NRF2-inducing phytochemicals, curcumin, improves exercise performance in mice with heart failure [ 166 ]. Moreover, genetic activation of NRF2 in skeletal muscles increases the slow oxidative muscle fiber type and improves exercise endurance capacity in female mice [ 167 ].…”
Section: Tissue Aging and The Keap1-nrf2 Systemmentioning
confidence: 99%
“…Recent studies have also clarified that appropriate activation of NRF2 has antiaging effects by limiting the accumulation of oxidative damage in tissues [ [8] , [9] , [10] ]. Moreover, NRF2 has been reported to confer resistance against mitochondrial toxins [ 11 , 12 ], protect against mitochondria-related disorders such as Parkinson's disease and Alzheimer's disease [ 13 , 14 ] and improve skeletal muscle performance and exercise endurance with increased oxygen consumption [ 15 , 16 ]. These reports suggest that NRF2 plays a crucial role in the regulation of mitochondrial function.…”
Section: Introductionmentioning
confidence: 99%
“…Another study demonstrated that improvement in aerobic capacity after forced treadmill running, which is observed in WT mice, is not observed in Nrf2 KO mice [ 36 ]. Recently, Keap1 deficiency, which activates the Nrf2 pathway, has been shown to enhance exercise capacity as well as force generation in mouse skeletal muscles [ 35 , 55 ]. Moreover, Sulforaphane treatment, which is known to activate Nrf2, increases running distance in an exhaustive treadmill running test in WT mice [ 53 ], and alleviates the reduction in grip strength and exercise capacity in mdx mice, the most widely used animal model of Duchenne muscular dystrophy [ 56 ].…”
Section: Nrf2 and Muscle Contractile Functionmentioning
confidence: 99%